Can high-speed train improve the innovation ability of enterprises? - Weilong Wu; Tang Jing; Yang Xiaoli (Journal of Applied Economics, 2022)
This paper analyzes the impact of high-speed train construction on enterprise innovation and its specific mechanisms by establishing high-speed train-city-firm level panel data and constructing a multi-period DID model in China. The results show that, firstly, the construction of a high-speed train significantly improves the innovation level of enterprises, and the construction of the first high-speed train can increase the number of patents of local listed enterprises by about 11.5%. Second, the impact of high-speed train construction on the innovation level of listed enterprises is mainly through the internal human capital and external marketization of enterprises. Specifically, the high-speed train construction affects innovation by weakening the transportation distance; on the other hand, it improves the external market environment and enhances the market competition, making firms seek innovation actively.
Keywords: 330; enterprise innovation; high-speed train; human capital; marketization level